Pengaruh Aplikasi Pembelajaran Online terhadap Hasil Belajar dan Motivasi Belajar Matematika Siswa Kelas XI SMA - Sappaile, Baso Intang; Rosidah, Rosidah; Mutmainna, Diati (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2024)
This study was conducted to effect of application online learning on motivation and mathematics achievement of student at grade XI SMA. This study is an quasi experiment study with a research sample 72 students from each one class XI SMA for the academic year 2021/2022 which were selected using the Stratified cluster random sampling technique. The instruments used observation of learning implementation, test achievement and scale motivation learning. The research data were analyzed by descriptive statistical analysis and inferential statistics by Independent Sample T-Test.the results showed that (1) The mathematics achievement at grade XI SMA of using application online learning (Google Classroom and WhatsApp Group) in high category and the motivation learning mathematics using application online learning (Google Classroom and WhatsApp Group) in high category. (2) There is difference using the Google Classroom online learning application with using the WhatsApp Group online learning application on the mathematics achievement of student at grade XI SMA. (3) There is difference using the Google Classroom online learning application with using the WhatsApp Group online learning application on the mathematics motivation of student at grade XI SMA.